2019
DOI: 10.1259/bjr.20190702
|View full text |Cite
|
Sign up to set email alerts
|

The FLASH effect depends on oxygen concentration

Abstract: Objective: Recent in vivo results have shown prominent tissue sparing effect of radiotherapy with ultra-high dose rates (FLASH) compared to conventional dose rates (CONV). Oxygen depletion has been proposed as the underlying mechanism, but in vitro data to support this have been lacking. The aim of the current study was to compare FLASH to CONV irradiation under different oxygen concentrations in vitro. Methods: Prostate cancer cells were irradiated at different oxygen concentrations (relative partial pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
194
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 40 publications
10
194
1
Order By: Relevance
“…Nevertheless, differences between tumor, normal cell metabolism and the microenvironment might provide some explanation for the FLASH effect. A recent report investigating FLASH and conventional dose rate irradiation has indicated the importance of oxygen tension in clonogenic survival assays (31), corroborating several past results (14,32). Increased oxygen tension afforded by carbogen breathing was also found to negate the neurocognitive benefits of FLASH, again suggesting a role for oxygen and ROS in the FLASH effect (14).…”
Section: Discussionsupporting
confidence: 70%
“…Nevertheless, differences between tumor, normal cell metabolism and the microenvironment might provide some explanation for the FLASH effect. A recent report investigating FLASH and conventional dose rate irradiation has indicated the importance of oxygen tension in clonogenic survival assays (31), corroborating several past results (14,32). Increased oxygen tension afforded by carbogen breathing was also found to negate the neurocognitive benefits of FLASH, again suggesting a role for oxygen and ROS in the FLASH effect (14).…”
Section: Discussionsupporting
confidence: 70%
“…The range of oxygen concentrations used in this study was relatively narrow (0.44-0.7% O 2 ) and therefore the phenomenon could have been limited to cells already in hypoxic environments. However, the recent in vitro study by Adrian et al used physiologically relevant oxygen concentrations (1.6-8.3% O 2 ) and showed that the sparing effect of FLASH irradiation is dependent on oxygen concentration (48). An in vivo mouse model has also shown that irradiation of mouse tails at ultra-high dose rates induced radioresistance indicative of oxygen depletion (49).…”
Section: Hypotheses To Explain the Flash Effect Oxygen Depletion Hypomentioning
confidence: 99%
“…12 Adrian et al reported that FLASH effect highly depends on the intracellular oxygen concentration, indicating the importance of the depletion and rediffusion of oxygen and/or radical-radical interaction for the FLASH effect. 13 This view was also pointed out over 60 years ago. 14,15 Under ionizing radiations, cells have been affected by the depletion of an oxygen-containing solute by radiation-chemical reactions, when replenishment by diffusion is insufficient.…”
Section: Introductionmentioning
confidence: 67%
“…In addition, the sparing effect observed under the FLASH condition. 13 The sparing effect was seen when the relative partial oxygen pressure was 4.4, 2.7 and 1.6%, namely under the hypoxia condition. In comparison to this, the sparing effect was not conrmed at the relative partial oxygen pressure of 8.8 and 20%.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation